2023
DOI: 10.1039/d3qm00146f
|View full text |Cite
|
Sign up to set email alerts
|

Coordination environment engineering of single-atom catalysts for the oxygen reduction reaction

Abstract: Benefiting from high efficiency and environmental friendliness, Zn-air batteries, fuel cells and the electrochemical H2O2 production have attracted significant attentions in the energy field. However, the oxygen reduction reaction (ORR),...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 199 publications
0
5
0
Order By: Relevance
“…86 Therefore, selectively integrating ISEs can immediately enhance ZAB performance. 87 The dual ISEE, equipped with a tuneable electronic structure and coordination environment, endows the ZAB with remarkable ORR and OER performances. For a deeper insight into the advantages, challenges, and improvement strategies, some representative studies reported during the last three years are surveyed below, categorised as Fe/Co-, Fe/Ni-, and Co/Ni-based electrocatalysts.…”
Section: Isees Application In Zabsmentioning
confidence: 99%
“…86 Therefore, selectively integrating ISEs can immediately enhance ZAB performance. 87 The dual ISEE, equipped with a tuneable electronic structure and coordination environment, endows the ZAB with remarkable ORR and OER performances. For a deeper insight into the advantages, challenges, and improvement strategies, some representative studies reported during the last three years are surveyed below, categorised as Fe/Co-, Fe/Ni-, and Co/Ni-based electrocatalysts.…”
Section: Isees Application In Zabsmentioning
confidence: 99%
“…In brief, achieving a comprehensive assessment of the environments surrounding M-N-C SACs necessitates the integration of multiple advanced characterization techniques. 112,113 A standout among these is aberration-corrected HAADF-STEM, a potent tool for visualizing SAs and their associated species, particularly those linked to metals. This technique offers valuable insights into spatial distribution and arrangement, thereby enhancing our understanding of the overall composition.…”
Section: Xas Analysismentioning
confidence: 99%
“…27–29 Notably, the ORR performance can be optimized by the modification of the coordination environments of atomic metal centers to regulate their electronic structures. 30 In recent developments, metal atoms, nanoclusters, and even nanoparticles have been coupled with Fe/Co–N x in Fe/Co–N–C SACs. This integration has yielded an enhanced electrocatalytic ORR performance of the obtained composites and promoted other functionalities, such as the oxygen evolution reaction (OER).…”
Section: Introductionmentioning
confidence: 99%